SYNTHESIS AND CHARACTERIZATION OF ZnO NANOPARTICLES: MINI REVIEW - Wulandari, Siti Aprilia; Hindryawati, Noor; Ashari, Irfan (PROSIDING SEMINAR KIMIA, 2023)
This mini review will explore the manufacture of ZnO nanomaterials. ZnO material has the advantages of high electron mobility, wide bandgap, high temperature resistance, and good UV absorption. ZnO has many applications in everyday life such as for photocatalysts, antibacterials, edible coatings, and others. Based on the literature review, ZnO material can be synthesized using sol-gel, hydrothermal, solvothermal, precipitation and coprecipitation methods. The resulting synthesis results are 7.4 nm-170 nm in size, have a hexagonal wurtzite crystal structure, have a bandgap of 3.23 eV-3.50 eV, and produce a surface area of 91.87 m2/g-113.37 m2/g. Based on the review conducted, it can be concluded that the method that produces ZnO nanoparticles with the smallest size and the largest surface area is synthesis using the solvothermal method. Keywords: Nano materials, Semiconductors, Nanoparticles.